2016
DOI: 10.3389/fpsyg.2016.01901
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Spanish Version of the Psychological Sense of School Membership (PSSM) Scale in Chilean Adolescents and Its Association with School-Related Outcomes and Substance Use

Abstract: School membership appears to be an important factor in explaining the relationship between students and schools, including school staff. School membership is associated with several school-related outcomes, such as academic performance and expectations. Most studies on school membership have been conducted in developed countries. The Psychological Sense of School Membership (PSSM) scale (18 items: 13 positively worded items, 5 negatively worded items) has been widely used to measure this construct, but no stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…This study investigated the factor structure of the PSSM on primary school populations and examined measurement invariance for three cross-cultural groups. Results of this study were similar to previous studies with adolescent students (Gaete et al, 2016;Hagborg, 1994;Ye & Wallace, 2014;You et al, 2011) and supported previous research, which showed that a reduced number of PSSM items can be used to measure students' sense of school belonging. Some may raise questions about whether this is a new instrument; however, this was not our intent.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study investigated the factor structure of the PSSM on primary school populations and examined measurement invariance for three cross-cultural groups. Results of this study were similar to previous studies with adolescent students (Gaete et al, 2016;Hagborg, 1994;Ye & Wallace, 2014;You et al, 2011) and supported previous research, which showed that a reduced number of PSSM items can be used to measure students' sense of school belonging. Some may raise questions about whether this is a new instrument; however, this was not our intent.…”
Section: Discussionsupporting
confidence: 90%
“…Investigating the use of the PSSM with primary school children is particularly important as perceptions of school membership and belonging begin at an early age (Lerner et al, 2018;Whitney & Smith, 1993) and may differ from adolescents. Additionally, despite its use in cross-national research (e.g., Cowden, Govender, Asante, Reardon, & George, 2016;Gaete, Montero-Marin, Rojas-Barahona, Olivares, & Araya, 2016;Ye & Wallace, 2014), the PSSM has not yet been subject to needed investigations regarding its invariance across sociocultural contexts. This article addresses these limitations by examining the PSSM in primary schools across three countries: The United States, China, and the United Kingdom.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there was one item with a factor loading lower than de recommended cut-off point (<0.32) [ 72 ], namely ‘good friends’ (0.25). This methodological effect has been found in the SDQ previously [ 40 , 73 ], and in other instruments [ 74 , 75 ]. In our study, these results may be explained by the cognitive development of people at this age (9–15 years old), who may have had difficulty understanding the answer format or the direction of the intercalated questions.…”
Section: Discussionsupporting
confidence: 67%
“…The Psychological Sense of School Membership Scale-Primary (PSSM-P; Wagle et al, 2018) is a recently developed modification of the original 18-item PSSM (Goodenow, 1993), which has been widely documented as a reliable and valid measure of school belonging, useful in various contexts (Cheung, 2004;Cowden, Govender, Oppong Asante, Reardon, & George, 2018;You, Ritchey, Furlong, Shochet, & Boman, 2011). The factor structure of the original scale was later examined with several studies finding that the negatively worded items formed their own factor and once these items were removed, a unidimensional factor structure of 11 items could be found (Gaete, Montero-Marin, Rojas-Barahona, Olivares, & Araya, 2016;Hagborg, 1998;Ye & Wallace, 2014;You et al, 2011). More recently, a nine-item unidimensional factor structure has been found sufficient to accurately grasp the school sense of belonging in primary school children, across different contexts-UK, China, and United States of America (Wagle et al, 2018), potentially providing a much more efficient way of screening for well-being levels in early years and allowing for screening in younger children.…”
Section: Methodsmentioning
confidence: 99%